Diversity of Ants (Formicidae) in the Bedengan Camping Ground Area, Malang Regency - Nanda Roudhotul R. P; Ratna Nur Chasanah; Arnita; Rizqi Khoirina; Florencia Arifika; Annisa Safira; Indra Fardhani (Jurnal Penelitian Pendidikan IPA, 2025)
Ant diversity (Formicede) plays an important role in the ecosystem, especially as an environmental indicator. This study aims to identify the diversity of ant species in the Bumi Camping area, Malang Regency, East Java, and to evaluate the factors that influence it. Ants have evolved into insects that are easily found in terrestrial ecosystems. Of the total number of insect species in the world, approximately 12.000 of them are ants, most of which are spread across tropical areas Data collection was carried out at six points around the musholla area using two trap methods, namely bait traps and fill traps. The ants caught were collected and identified using a stereo microscope, determination keys, and supporting applications. The study found 9 different ant species, including Paratrechina longicornis. Camponatus atriceps, and Monomorium pharaonis. The diversity of ant species is influenced by environmental factors such as altitude, humidity, and food availability. The results showed that the study area had a low diversity index value, possibly due to antibiotic factors and land conversion. This study contributes to the understanding of ant diversity in tropical areas and the importance of ant habitat conservation in forest ecosystems.